Molecular Mechanisms of Druze Formation in the Retina in Age-Related Macular Degeneration - E. F. Barinov (Oftalʹmologiâ)
Age-related macular degeneration is the main cause of vision loss in aged people. A significant risk factor of disease is considered dysfunction of retinal pigment epithelium, which is accompanied by accumulation of lipids in Bruch membrane as drusen or linear deposits. As a result, there are disturbance of substances and oxygen transport from blood to retina cells of eye as well as elimination of toxic catabolites to choroid capillaries. The lack of a systematic analysis of pathogenetic mechanisms of drusen’s formation in age-related macular degeneration controls possibility of developing methods for treating and preventing development of early stage of age-related macular degeneration. There are the data of risk factors and pathogenesis of age-related macular degeneration in the article. It pays attention to the significance of oxidative stress in pigment epithelium of macula and triggering factors of inflammation development in eye retina. In context of differences in lipid composition and topographic location of cones and rods photoreceptor cells the localization of drusen, basal laminar and linear deposits in Bruch membrane is discussed. The possible mechanisms of drusen biogenesis associated with  functioning of cholesterol carriers and lipid autophagy in retinal pigment epithelial cells as well as the role of  macrophages in transport of local cholesterol depot to systemic circulation are presented. Analysis of literature allowed to identify several promising areas of development of targeted therapy for lipid metabolism disorders in  retina. They include the reactivation of lipid carriers in RPE cells, ligand-receptor mechanisms that provide a reduction pH in lysosomes and maintaining functional activity of macrophages.